Movimento GLBT: considerações necessárias - Fernando José Taques (Ciências Sociais Unisinos)
This article reflects on current issues involving the struggle for rights by GLBTs (Gays, Lesbians, Bisexuals and Transgenders) in Brazil and other countries and points out accomplishments and setbacks experienced by GLBT Movement. On the basis of dialogues with various authors, it discusses the peculiarities of the GLBT Movement and its implications for democracy and citizenship as well as its constant openness towards inclusion.